Phase I Study of the Pharmacodynamics and Safety of Sodium Zirconium Cyclosilicate in Healthy Chinese Adults. Issue 3 (8th January 2022) - Cheung, Tommy; Sun, Fang; Zhao, June; Qin, Yulin; Någård, Mats
Abstract: Sodium zirconium cyclosilicate (SZC) is an effective potassium binder for patients with hyperkalemia. This single‐center, open‐label, phase I study (NCT03283267) characterized the pharmacodynamics and safety of SZC in Chinese individuals. Twenty‐two healthy Chinese adults (mean age, 33.5 years) randomized 1:1 received daily oral SZC 5 or 10 g for 4 days, following 4 days on a low‐sodium, high‐potassium diet (continued throughout the study). End points were mean change from baseline in 24‐hour urinary potassium (primary) and sodium excretion, and serum potassium concentration. Urinary potassium excretion significantly decreased with SZC 5 g (mean change [mmol], –13.0; P < .001) and 10 g (–15.4; P < .001). Although urinary sodium excretion decreased significantly with SZC 5 g (–11.5; P = .030), there was no significant change with SZC 10 g (–5.1; P = .299). Serum potassium concentrations decreased significantly with SZC 5 g (–0.14; P = .031) and 10 g (–0.20; P = .002). All treatment‐emergent adverse events were mild, and none were considered causally related to SZC. Over 4 days, the pharmacodynamics and safety of SZC were consistent in healthy Chinese adults with global studies and patients of Japanese ethnicity.